Intestinal parasites in children with neoplasms - Aksoy, Umit; Erbay, Ayşe; Akisu, Ciler; Apa, Hurşit; Ozkoç, Soykan; Oztürk, Sevinç (The Turkish Journal of Pediatrics, 2003)
Stool specimens taken from 50 children with malignancy and from 92 healthy children were investigated for intestinal parasites, using the modified formol ethyl acetate concentration method, and native-lugol, trichrome and Kinyoun acid-fast stain methods. Thirty-eight (76.0%) of the 50 patients had lymphoma or leukemia and were considered immunosuppressed. Several different parasites were found in 21 (42.0%) of the 50 patients with malignancy and in 16 (47.3%) of the 38 patients with immune deficiency compared to in only 16 (17.3%) of the 92 healthy children. The incidence of parasites in patients with malignancy or immunosuppression was significantly higher than in the healthy control group (p